Sarcasm In Virtual Communication Of Mobile Legends Gameplay On Youtube - Muhammad Ilfan; Yanto Yanto; Sapta Sari (Multidisciplinary Journals, 2026)
This study aims to analyze the use of sarcasm in virtual communication within Mobile Legends gameplay content on YouTube, particularly on the @PascolKintil channel. The development of digital communication through social media platforms enables interaction without face-to-face contact, influencing how individuals express opinions, emotions, and criticism through language. This research employed a descriptive qualitative approach based on Computer Mediated Communication (CMC) theory to examine how sarcastic expressions appear in digital gaming interactions. Data were collected through non-participant observation of two selected YouTube videos and documentation of verbal expressions that contain sarcasm. The analysis process involved data reduction, data presentation, and interpretative conclusion drawing. The results show that sarcasm functions not only as a form of criticism and humor but also as a strategy for expressing frustration, reducing tension during gameplay, strengthening team solidarity, and building digital identity within online gaming communities. In virtual communication contexts where non-verbal cues are limited, sarcastic meanings rely heavily on textual and verbal expressions as well as shared contextual understanding among players and audiences. The study concludes that sarcasm represents an adaptive communication strategy that shapes interaction patterns and digital communication culture among online gaming communities on YouTube.